Cultivating the uncultured: Harnessing the “sandwich agar plate” approach to isolate heme‐dependent bacteria from marine sediment - Jing Zhang; Qi‐Yun Liang; Da‐Shuai Mu; Fengbai Lian; Ya Gong; Mengqi Ye; Guan‐Jun Chen; Yuqi Ye; Zong‐Jun Du (mLife, 2024)
Abstract In the classical microbial isolation technique, the isolation process inevitably destroys all microbial interactions and thus makes it difficult to culture the many microorganisms that rely on these interactions for survival. In this study, we designed a simple coculture technique named the “sandwich agar plate method,” which maintains microbial interactions throughout the isolation and pure culture processes. The total yield of uncultured species in sandwich agar plates based on eight helper strains was almost 10‐fold that of the control group. Many uncultured species displayed commensal lifestyles. Further study found that heme was the growth‐promoting factor of some marine commensal bacteria. Subsequent genomic analysis revealed that heme auxotrophies were common in various biotopes and prevalent in many uncultured microbial taxa. Moreover, our study supported that the survival strategies of heme auxotrophy in different habitats varied considerably. These findings highlight that cocultivation based on the “sandwich agar plate method” could be developed and used to isolate more uncultured bacteria.